Glycoprotein IIb/IIIa antagonists - Zeymer, U.; Zahn, R. (Hämostaseologie, 2009)
The role of GP IIb/IIIa antagonists has been focused on patients with acute coronary syndromes undergoing PCI. In the ISAR-REACT 2 study abciximab given in patients with NSTEACS undergoing PCI already treated with 600 mg clopidogrel improved 30-day death and reinfarction rate in troponin positive patients. In the large EARLY-ACS trial upstream therapy with eptifibatide in high risk with NSTE-ACS did not improve ischaemic complications but was associated with an increase in bleeding complications. Therefore GP IIb/IIIa antagonists should be given after the initial angiography and the decision the perform PCI in troponin positive patients with NSTE-ACS.In patients with STEMI undergoing primary PCI the prehospital administration of tirofiban was associated with an improved myocardial reperfusion. In contrast in the BRAVE 3 trial abciximab in patients with pretreatment with 600 mg clopidogrel did not reduce infarct size or improve clinial outcome. Comparative trials evaluating the effectiveness of abciximab and the small molecules tirofiban and eptifibatide did not show any differences between the three GP IIb/IIIa antagoniosts.
Keywords: Acute coronary syndromes; percutaneous coronary intervention; GP IIb/IIIa antagonists; clinical trials